Design of Compresion Sensor by Zno Substrate using Precipitation Method - Kavitha, A; N.Swaminathan, J; Ashok Kumar, N (International Journal of Engineering and Technology, 2018)
The Zinc Oxide nanoparticles are synthesized by the precipitation method using zinc acetate dehydrate and sodium hydroxide. The significance of characterization techniques like AFM, SEM, FTIR Spectrum and XRD for the prepared nanomaterial is studied. The prepared nanoparticles are used to improve the electrical conductivity of dielectric polymer like PMMA. Polymer metal Nano composites are prepared by in-situ oxidative polymerization of Methyl methacrylate monomer in the presence of different concentration of prepared metal nanoparticles. The electrical conductance is investigated using multimeter. The conductivity of the dielectric polymer is found to be increased with the increasing semiconductor concentration. Based on the result the prepared Nano composites can be used to convert the insulating foam into conductive one which can used to fabricate compression sensor.